Revisiting the role of self-control in Situational Action Theory. (January 2018) - Kroneberg, Clemens; Schulz, Sonja
Wikström's Situational Action Theory of Crime Causation (SAT) aims at providing a comprehensive account of the action-generating mechanisms that underlie rule-breaking. Paying tribute to the longstanding criminological interest in self-control, SAT also entails a new view of this concept and its role in crime causation. SAT claims that morality is the more fundamental determinant of rule-breaking and that self-control should become relevant only when actors enter a process of deliberation on whether or not to break a rule. Our contribution is twofold: theoretically, we discuss the role of self-control in SAT and derive previously untested implications; empirically, we evaluate these implications based on data from a large German panel study and thereby advance our understanding of when and how self-control matters for crime and delinquency.